Induction of apoptosis and cell cycle arrest by chloroform fraction of Juniperus phoenicea and chemical constituents analysis - Barnawi Ibrahim O. (De Gruyter, 2021)
Different phytochemicals from various plant species exhibit promising medicinal properties against cancer. Juniperus phoenicea is a plant species that has been found to present medicinal properties. Herein, crude extract and fractions of J. phoenicea were examined to determine its anticancer properties against several cancer cells. The active fraction was chosen to assess its activity on cell cycle progression and apoptosis induction by annexin and propidium iodide (PI) biomarkers. Further, phytochemical screening for possible contents of active fraction using gas chromatography–mass spectrometry (GC-MS) analysis was conducted. It was demonstrated that cell proliferation was suppressed, and the MCF-7 cell line was the most sensitive to J. phoenicea chloroform fraction (JPCF), with the IC50 values of 24.5 μg/mL. The anti-proliferation activity of JPCF in MCF-7 cells was linked to the aggregation of cells in the G1 phase, increases in early and late apoptosis as well as necrotic cell death. Contents analysis of JPCF using GC-MS analysis identified 3-methyl-5-(2′,6′,6′-trimethylcyclohex-1′-enyl)-1-penten-3-ol (16.5%), methyl 8-oxooctanoate (15.61%), cubenol (13.48%), and 7-oxabicyclo [2.2.1] heptane (12.14%) as major constituents. Our present study provides clear evidence that J. phoenicea can inhibit cell proliferation, trigger cell cycle arrest, and induce apoptosis in tested cancer cells.